CRIMINAL-EXECUTIVE PRINCIPLES OF ENCOURAGING LAW-ABIDING BEHAVIOR IN CONVICTED PERSONS DURING THE SERVING OF SENTENCES - Bogatyrov, Ivan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to conduct a comprehensive study of the criminal-executive foundations for stimulating law-abiding behavior among convicted persons during the execution of sentences, as well as to determine the role of incentives, disciplinary measures, and social correction programs in forming sustainable motivation to comply with legal norms. Research methods: the research applies formal-legal, system-structural, comparative-legal methods, as well as the method of theoretical generalization. The conclusions are based on the analysis of the criminal-executive legislation of Ukraine, scientific works of domestic scholars, and the practical activities of penitentiary institutions. The results: it has been established that the principle of stimulating law-abiding behavior is based on the principles of humanism, differentiation, and individualization of sentence execution. It is substantiated that the effectiveness of this principle is ensured through the complex application of: 1) incentives, which contribute to building positive motivation and behavioral change (gratitude, rewards, improved conditions of detention, participation in self-governing organizations, etc.); 2) disciplinary measures, which must be proportionate to the committed misconduct and aimed at restoring discipline; 3) social correction programs, which take into account the individual characteristics of convicted persons and contribute to their resocialization and future reintegration. It has been identified that under martial law, penitentiary institutions become more vulnerable, which increases the relevance of studying and practically implementing mechanisms for stimulating law-abiding behavior. Discussion: the results confirm that stimulating law-abiding behavior should be considered not merely as an encouragement mechanism but as a comprehensive legal instrument combining elements of coercion, social correction, and educational influence. Emphasis is placed on the need to improve legal norms regulating incentives and disciplinary measures, as well as the importance of a personalized approach to each convicted person. It is argued that the implementation of this principle is a key condition for achieving the purpose of punishment defined by the Criminal Code of Ukraine and for ensuring security within penitentiary institutions during the period of martial law.